A pharmacological appraisal of medicinal plants with antidiabetic potential - Vasim Khan; Abul Kalam Najmi; Mohd. Akhtar; Mohd. Aqil; Mohd. Mujeeb; K K Pillai (Wolters Kluwer Medknow Publications, 2012)
Diabetes mellitus is a complicated metabolic disorder that has gravely troubled the human health and quality of life. Conventional agents are being used to control diabetes along with lifestyle management. However, they are not entirely effective and no one has ever been reported to have fully recovered from diabetes. Numerous medicinal plants have been used for the management of diabetes mellitus in various traditional systems of medicine worldwide as they are a great source of biological constituents and many of them are known to be effective against diabetes. Medicinal plants with antihyperglycemic activities are being more desired, owing to lesser side-effects and low cost. This review focuses on the various plants that have been reported to be effective in diabetes. A record of various medicinal plants with their established antidiabetic and other health benefits has been reported. These include Allium sativa, Eugenia jambolana, Panax ginseng, Gymnema sylvestre, Momrodica charantia, Ocimum sanctum, Phyllanthus amarus, Pterocarpus marsupium, Trigonella foenum graecum and Tinospora cordifolia. All of them have shown a certain degree of antidiabetic activity by different mechanisms of action.